Comparison between standard hematological parameters and blood doping biomarkers in dried blood spots within the athlete population of Swiss Sport Integrity - Oliveira, Jessica Almeida; Loria, Francesco; Schobinger, Céline; Kuuranne, Tiia; Mumenthaler, Claudia; Leuenberger, Nicolas (Frontiers in Sports and Active Living, 2024)
Introduction The study demonstrated the feasibility of incorporating RNA biomarkers, specifically 5-aminolevulinic acid synthase (ALAS2) and carbonic anhydrase 1 (CA1), to improve the hematological module of the Athlete Biological Passport (ABP) in routine antidoping context. Objective The aim was to investigate the implementation of reticulocyte (RET) related biomarkers, specifically ALAS2 and CA1, using quantitative reverse transcription polymerase chain reaction (RT-qPCR) on dried blood spots (DBS) from elite athletes. Hemoglobin changes over time in DBS samples was measured as well. Combining hemoglobin and messenger RNA (mRNA) analyses allowed to monitor alterations of the established marker, “DBS OFF-score”. Methodology Ten athletes were selected for sampling by the Swiss national antidoping organization, Swiss Sports Integrity (SSI). Samples were collected, transported and analyzed for ABP following the World Anti-Doping Agency (WADA) procedures and spotted onto Protein Saver DBS cards. Results Most athletes exhibited stable biomarker levels, except for one individual involved in ski mountaineering, who demonstrated a sustained increase in ALAS2 compared to the individual baseline. This elevation could be due to blood withdrawal or other factors, such as doping with substances outside the targeted test menu. Conclusion In this study, RNA-biomarkers were successfully analyzed in routine blood samples, and the project demonstrated promising results for the implementation of ALAS2 and CA1 in routine analysis to complement the ABP.